L-Tetrahydropalmatine, a Novel Dopamine Antagonist, Fails to Improve Psychiatric Symptoms as Adjunctive Treatment for Schizophrenia. Issue 1 (25th May 2020) - Ponomareva, Olga Y; Redman, Brianne; Sayer, MacKenzie A; Wehring, Heidi J; Vyas, Gopal; Richardson, Charles M; Gold, James M; Gorelick, David A; Cihakova, Daniela; Talor, Monica V; Hoag, Stephen W; Buchanan, Robert W; et al.
Abstract: Schizophrenia is a complex mental illness characterized by positive and negative symptoms. Antipsychotic medications are the main treatment for this condition; however, many patients have only a partial response. All currently available antipsychotics involve modulation of the dopamine system, although the underlying pathophysiology of this illness remains poorly understood. Increasing evidence suggests that inflammation plays a significant role in the development of schizophrenia. Thus, a medication that modulates both dopamine signaling and inflammation may be a promising treatment for schizophrenia. L-tetrahydropalmatine (l-THP) has modest affinity for dopamine receptors, acting as an antagonist at D1, D2, and D3 receptors. L-THP also has anti-inflammatory effects, decreasing levels of tumor necrosis factor-α and interleukin 6. We performed a 4-week, randomized, double-blind, placebo-controlled trial of oral l-THP (30 mg twice daily) as an adjunctive treatment in 63 adults with schizophrenia ( Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria) on stable antipsychotic medication. The primary psychiatric outcome measures were the presence of positive and negative symptoms. Plasma concentrations of 11 cytokines and C-reactive protein (CRP) were also measured. L-THP had no significant effect on any psychiatric measure but was well tolerated and associated with a significant decrease in extrapyramidal symptoms. L-THP significantly increased plasma concentrations, compared with placebo, of two inflammatory markers: soluble intracellular adhesion molecule 1 and CRP. These findings do not support the efficacy of L-THP as an add-on treatment for schizophrenia but suggest that L-THP may have previously unrecognized proinflammatory effects in people with this disease.